An American in His Native Land: John Cournos in Petrograd - Marilyn Schwinn Smith (Journal of Russian American Studies, 2022)
This article builds upon Marilyn Schwinn Smith's previous work (published in JRAS vol 5, no. 1, 2022). It continues the story of Russian-Jewish American writer and translator John Cournos (1881-1966) and his experiences in revolutionary Petrograd from October 1917 to March 1918. Invited to join the British Anglo-Russian Commission as a cultural propagandist, Cournos witnessed the turbulent political landscape and human suffering of the Russian Revolution. His story captures a microcosm of complicated wartime Allied relations through the lens of an observer intertwined in politics and the literary arts. This article, combining political, literary, and cultural history, also highlights Cournos’s encounters with prominent literary figures, including Anna Akhmatova, and the lasting impact of Petrograd’s upheaval on his literary contributions and perceptions of revolution​. Note- For Part 1 of this article see Marilyn Schwinn Smith, “John Cournos Among the Imagists: Prelude to Petrograd,” JRAS 5, no. 1 (2021). [https://doi.org/10.17161/jras.v5i1.15436]